The Effect of Price Balance And Location On Consumer Purchase Interest In The Bode Lor Caplek Market - Diyanah Zulfa; Afiqoh Agustin; Achmad Otong Bushtomi (Cirebon International Journal of Economics and Business, 2024)
Bode Lor Caplek Market is a long-established village market on Kisabalanang Street. Bode Lor Village is famous for the woven fabric trade, the traders utilize the shoulder of the road to be used as a place for them to make a living. Then, because it causes congestion, the Bode Lor Village government provides facilities in the form of kiosks so that traders can sell in an orderly manner. In 2023 the Bode Lor Caplek Market was developed into a semi-modern market, formerly known as the source of congestion in Bode Lor Village. The revitalization of the modern art market resulted in 320 stalls and stalls with 282 traders. Caplek Bode Lor Market has a Vision and Mission, namely "Improving and Prospering the Community Economy through the Market Self-Management Program". The market as a means of support for the community to fulfill their needs in their survival. The market is a place where buying and selling transactions for goods or services occur. The development of modern markets has made the economic sector experience significant changes. However, until now traditional markets are still in great demand by the community. in compensating for the quality of modern markets, the government is self-managing the market through a traditional market revitalization program to make it more attractive to visitors.